Smart irrigation system based on internet of things with voice command - Karakhan, Hussein Amer (School of Computer and Communication Engineering, 2019)
Due to time limitations, it has been decided to orient this project to accomplish two (2) goals. First, is to develop an irrigation system that reduces water usage. The system will use the dripping method instead of sprinkling method to irrigate water as dripping helps to reduce water more compared to sprinkling. Second is to develop an application system to assist farmers and gardeners monitor their land.